First Report on Wild Ginger (Family: Zingiberaceae) Species Composition with New Records in Limestone Forests of Kelantan, Peninsular Malaysia - Suganthi Appalasamy,; Nivaarani Arumugam,; Nor Syahaiza Ahmad Zamri,; Anis Fadhlina,; Jayaraj Vijaya Kumaran ,; Sreeramanan Subramaniam, (Tropical Life Sciences Research, 2022)
The wild gingers in the family Zingiberaceae have a wide range of habitat distribution. The species growing in Malaysian forests are the most studied. Nevertheless, the aromatic perennial herb family found in limestone forests is the least studied. The present study identified the ginger species compositions, determined the conservation status of the identified ginger species, and compared the distribution of the ginger species in selected limestone forests of Kelantan due to the lack of intensive study focusing on wild gingers in Malaysian limestone forests, especially in the state of Kelantan, to date. In various months, wild ginger species observation was conducted at four limestone forests in Kelantan. From the survey performed during the present study, Gua Setir and Gua Ikan recorded 16 species with 12.5% overlapping species. Gua Setir comprised 61.5% more ginger species than Gua Ikan. In total, 13 species (81.25%) were evaluated based on the Red List of Threatened Species by the International Union for Conservation of Nature (IUCN). Three wild ginger species listed as high conservation value (HCV), Zingiber aurantiacum, Zingiber petiolatum, and Zingiber wrayi, were identified at the limestone karst valley of Gua Setir. The current study presented updated and new records of the limestone wild ginger flora in Kelantan. The research also demonstrated that each limestone forest consisted of different combinations of ginger species. Consequently, conservation efforts and sustainable management currently enforced in the limestone forests would lead to long-term protection of the plants. Furthermore, the wild gingers could become a tourist attraction for limestone forests located in recreational areas. Halia hutan (Famili: Zingiberaceae) mempunyai taburan habitat yang luas. Kajian mengenai tumbuhan herba yang berbau harum ini kurang dilakukan di kawasan hutan batu kapur Malaysia. Kajian ini telah mengenal pasti komposisi spesies halia, menentukan status pemuliharaan spesies halia yang telah dikenal pasti, serta membandingkan taburan spesies halia di beberapa hutan batu kapur di Kelantan. Kajian ini juga dilakukan kerana kekurangan kajian intensif yang memfokuskan halia hutan di hutan batu kapur Malaysia, terutamanya di negeri Kelantan, sehingga kini. Pemerhatian terhadap spesies halia hutan telah dilakukan di empat hutan batu kapur di Kelantan. Gua Ikan dan Gua Setir telah merekodkan 16 spesies halia semasa pemerhatian tersebut dengan 12.5% spesies yang bertindih. Gua Setir merangkumi 61.5% spesies halia berbanding Gua Ikan. Secara keseluruhan, 13 spesies (81.25%) halia yang dikenal pasti telah dinilai berdasarkan Red List of Threatened Species oleh International Union for Conservation of Nature (IUCN). Sebanyak tiga spesies halia telah disenaraikan sebagai spesies high conservation value (HCV) iaitu Zingiber aurantiacum, Zingiber petiolatum dan Zingiber wrayi. Ketiga-tiga spesies ini telah dikenal pasti di lembah kars Gua Setir. Kajian ini telah memberikan rekod spesies yang telah dikemaskini serta rekod baru bagi spesies halia hutan di kawasan batu kapur di Kelantan. Kajian ini juga menunjukkan bahawa setiap hutan batu kapur terdiri daripada gabungan spesies halia yang berbeza. Oleh yang demikian, usaha pemuliharaan dan pengurusan mampan yang dilakukan pada masa kini di hutan batu kapur akan membawa kepada perlindungan jangka panjang untuk tumbuhan halia. Tambahan pula, tumbuhan halia hutan juga boleh dijadikan sebagai tarikan pelancong untuk hutan batu kapur di kawasan rekreasi.